1986
DOI: 10.1016/s0022-5347(17)44928-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Cholinergic Muscarinic Responsiveness and Receptors in the Rat Urinary Bladder

Abstract: The effects of age on urinary bladder responsiveness to muscarinic agonists and on the Bmax and Kd of the binding of [3H]quinuclidinyl benzilate (QNB) to muscarinic receptors of the bladder were studied. Bladder bodies and bases were isolated from Fischer 344 rats, ages seven, 16 and 27 months. No age-dependent change in maximum KCl-elicited isotonic contractions was observed in either bladder region. The bladder base showed an age-dependent increase in the maximum contractions (Emax) elicited by muscarinic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
3
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 16 publications
4
22
3
1
Order By: Relevance
“…These results indicate that bladder contraction via voltage-dependent Ca 2+ channel was not affected in aged rat. In accordance with the present study, it is reported that KCl-induced isotonic contraction was not altered by aging [7,9]. …”
Section: Changes In the Kcl-induced Bladder Contraction In Aged Body supporting
confidence: 93%
See 1 more Smart Citation
“…These results indicate that bladder contraction via voltage-dependent Ca 2+ channel was not affected in aged rat. In accordance with the present study, it is reported that KCl-induced isotonic contraction was not altered by aging [7,9]. …”
Section: Changes In the Kcl-induced Bladder Contraction In Aged Body supporting
confidence: 93%
“…Several reports indicated that both alpha-adrenergic receptor and muscarinic receptor existed not only in bladder body but also in trigone [6][7][8]. However, there are no confidential results whether α-adrenergic as well as muscarinic receptors play a role in age-related functional changes of urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, there have been only a few reports that age affects mus carinic cholinergic receptors in the rat prostate. Three reports (29)(30)(31) have examined muscarinic receptors in the aging rat urinary bladder. Two showed an increase (29,30) in the density of receptors, while the other showed no change (31).…”
Section: Discussionmentioning
confidence: 99%
“…Three reports (29)(30)(31) have examined muscarinic receptors in the aging rat urinary bladder. Two showed an increase (29,30) in the density of receptors, while the other showed no change (31). However, these discrepancies might be explained by possible differences in the nature of the tissue samples and/or rat strain.…”
Section: Discussionmentioning
confidence: 99%
“…There is a heterogeneous population of muscarinic receptor subtypes in many tissues, including the urinary bladder. A predominance of the M 2 receptor subtype along with a smaller population of M 3 receptors has been observed in the urinary bladder smooth muscle (15). Although both receptors influence contraction of the detrusor muscle, the M 3 receptor appears to be the most functionally important, as it mediates direct contraction of the detrusor muscle (4).…”
Section: Discussionmentioning
confidence: 99%